An online education program for improving parent’s knowledge of appropriate complementary feeding and child health - Rachmawati Widyaningrum; Fredeswindra Elievia Chintyasningrum Wienarno; Nurul Jamilah (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2022)
During the Covid-19 pandemic, its socio-economic impact can disrupt children's state of well-being as a vulnerable group. The changes in income and difficulties in accessing healthy and affordable food may affect the complementary feeding (CF) practices, and affect a child's nutritional status, and immunity. Besides, the lack of CF knowledge results in an increment in commercial supplement consumption to patch up nutrient deficiencies or prevent transmission. In this regard, the education program about healthy complementary feeding is essential. The online education program titled "Healthy Complementary Feeding to Protect Child's Health" was attended by 17 of 60 registrants (23,8%). It aimed to improve CF knowledge based on the WHO recommendation on CF, including local food-based CF  The program's evaluation results show that the major of the participants were satisfied, 60% of them strongly agreed that it was informative, and 75% of them strongly agreed that the materials were easy to understand. The follow-up results of 14 participants show that the CF knowledge score increased by 10.5% (The before-after mean score). The topic of children refusing to eat was the most beneficial topic for participants (92.9%). The conclusion is that an online-based education program in the pandemic setting can increase the participant's CF knowledge.